RESTRUKTURISASI KETENAGAKERJAAN DALAM PROSES MODERNISASI BERDAMPAK PERUBAHAN SOSIAL PADA MASYARAKAT PETANI - ROOSGANDHA ELIZABETH (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Sugar, one of the commercial plant state commodity for Indonesia; which are the necessaryfor human being, under any circumstances. But, sugar cane cause the land more tight to getrid of these difficult problems, by conducting “Tebu Rakyat Intensifikasi” programs. Thesepurpose of research, to know about the labor concerning income, trend, and therestructurization become of labor transformation, which were depended the social changeon social, economics, culture and politics trend of the sugar cane peasant, at Langkat andDeli Sedang districts, North Sumatera. “P.G” Kuala Madu is the cane industrymanufactory, which the “TRI” program’s applied. The labor interaction caused the manysocial change problems. : “Social change is the significant alteration of social structurethrough time”. “Social structure means a persistent network of social relationships in whichinteraction gas become routine and repetitive”. (Harper, 1989). Sugar cane farming system,to increasing sugar cane productivity and farmer (peasant) incomes by “TRI” policyprogram, and aspect of it for competitive influence ability and sugar selling price ininternational market and domestic market. The identifying problems of sugar factory suchBUMN’s inefficiency ; institution infractions, the weakness or dilated of governance toanticipatory the implication of many other sugar cane problem. Aim, the restructurizationon labor of sugar cane farmers need government attended and, the restructurization of sugarfactory should be directed to share owning removement to farmers of sugar cane.